Exploring the transition of undergraduate medical students into a clinical clerkship using organizational socialization theory - Atherley, Anique E. (Perspect Med Educ, 2016)
BACKGROUND: Transitions in medical education are emotionally and socially dynamic; this may affect learning. Students transitioning from preclinical to clinical training may experience negative consequences. Less is understood about students’ experiences during transitions within clinical training and influential factors. METHODS: The authors used organizational socialization theory to explore a transition within the clinical years. Final-year medical students experienced a nine-week internal medicine clerkship; willing students participated. Students (n = 101; 97 %) completed a questionnaire with open-ended questions at the beginning and end of the clerkship and participated in six consecutive focus groups, until data saturation occurred (n = 37). Data were thematically analyzed. RESULTS: Socialization was challenging. Many students experienced difficulty developing relationships with team members. Students with a positive attitude experienced a smoother transition. Many students were uncertain of their roles, concerned about the workload and desired guidance to meet clerkship demands. This transition resulted in varied outcomes from enjoyment, increased confidence and student development through to disinterest. CONCLUSION: Transitions within clinical training are complex. Faculty should focus on adequate socialization in a new clerkship as this may facilitate a smoother transition. This may necessitate orientations, staff training, and formal student support. Further research is needed on the impact of these recommendations on learning and well-being.